Length–weight relationship of Rhinobatos horkelii Müller & Henle, 1841 and Zapteryx brevirostris (Müller & Henle, 1841) off Brazil, southwestern Atlantic Ocean - Pasquino, A. F. [UNESP]; Martins, M. F. [UNESP]; Gadig, O. B.F. [UNESP] (Hindawi, 2016)
This study reports the length–weight relationships (LWRs) for two elasmobranch species, Rhinobatos horkelii Müller & Henle, 1841 and Zapteryx brevirostris (Müller & Henle, 1841) collected from the southwestern Atlantic, off Brazil. Both are considered endangered species. The LWR data can be taken into consideration for further management and conservation plans.